A consistent description of the kinetic processes of electrolyte ion transport in a dynamic porous medium - P. P. Kostrobij; B. M. Markovych; O. V. Viznovych; M. V. Tokarchuk (Condensed Matter Physics, 2025)
The consistent description of kinetic and hydrodynamic processes is applied to the study of ion transport processes in the ionic solution-porous medium system.  A system of equations is obtained for the nonequilibrium single-ion distribution function, the nonequilibrium average value of the energy density of the interaction of solution ions, and the nonequilibrium average value of the number density of particles in a porous medium.  Using the fractional calculus technique, a generalized diffusion equation of the Cattaneo type in fractional derivatives is obtained to describe the processes of subdiffusion of particles in a porous medium.